Data on the involvement of Meox1 in balloon-injury-induced neointima formation of rats - Wu, Bing (Data Brief, 2017)
In the previous report, Meox1 was found to promote SMCs phenotypic modulation and injury-induced vascular remodeling by regulating the FAK-ERK1/2-autophagy signaling cascade (Wu et al., 2017) [1]. Here, we presented new original data on the involvement of Mesoderm/mesenchyme homeobox gene l (Meox1) in balloon-injury-induced neointima formation of rat. In rat carotid artery balloon injury model to induce vascular remodeling, Meox1 was induced in vascular smooth muscle cell (SMCs) of rat carotid arteries. Most proliferating cell nuclear antigen (PCNA)-positive cells also expressed Meox1. These data suggested that Meox1 may be involved in SMCs proliferation during injury-induced neointima formation. Furthermore, knocked down its expression in injured arteries by adenoviral delivery of Meox1 short hairpin RNA (shRNA) (shMeox1), neointima formation was significantly inhibited. Elastin staining also confirmed the reduction of neointima in Meox1 shRNA-transduced arteries. Moreover, knockdown of Meox1 decreased the collagen production/deposition that was significantly increased in neointima induced by balloon injury.